Terço dos homens de Brasília Teimosa : identidade, gênero e subjetividade - Santos, Fabiana Maria dos (2014)
The male devotion around the rosary prayer has inspired the birth of several groups in parishes around the world. Through the experience of faith, devotees of the Mother Queen of Schoenstatt leaves the anonymity, calling the men of the communities to participate more in religious life to experience the sacred . This thesis is an ethnographic study about a movement that has contributed to the construction of a Catholic identity through male participation. The aim of this study was within the postmodern social context that involves the periphery of Recife, analyze the religious group the Rosary of Men, through its history, its conflicts, its relationship with the divine, clothed with the forms of maternal mediation of Our Lady. What takes men of different backgrounds to unite around this practice of faith? What motivates them to meeting weekly to pray the Rosary? What does return and remain in the Church? These were some questions that guided this research. After this study, it was confirmed that the search for the sacred is an important part in human walking, the reconstruction of gender identities and subjectivity amid the crisis of social transformation, the humanization of each and also the universe that surrounds you.